Design of fiber optic transceiver for RF link - Xiao, Shouyan (2014)
Radio over Fiber refers to a technology where fiber cable is the media to transmit radio signals from base station to remote station for wireless communications. As compared to one of the transmission media coaxial cable, fiber cable has many advantages, such as low attenuation loss, large bandwidth and immunity to radio frequency interference. Therefore, it is widely used in in-building antenna remote systems.